Measurement of weight of objects without affecting the handling algorithm. (30th September 2016) - Sukop, Marek; Hajduk, Mikuláš; Semjon, Ján; Jánoš, Rudolf; Varga, Jozef; Vagaš, Marek
The article is devoted to understand how to easily perform weight measurement of the workpiece in the course of handling the robot cycle, provided that the handling cycle of the robot is not a sufficient idle time. It is therefore necessary to find a time gap in the algorithm of motion, which would be suitable for such a measurement. This place is affected by the handling speed, acceleration, grip stability of the workpiece – it is necessary to exclude other dynamic effects on the measurement of weight. The authors suggest that one of the best ways to avoid systematic errors is to find a sufficiently large acceleration in the positive direction of the axis 'z' of the handling robot. The article describes how the authors performed a few weight measurements of the pieces in the dynamic mode, and finally the evaluating the accuracy of the calibration measurements with the help of the used measuring chain.